Estado nutricional relacionado con el desempeño académico de los niños preescolares de la escuela Manuel José Rodríguez - Palacio Jaramillo, María Belén (2022)
Nutrition is defined as a biological process in which ingested food is used to protect the body and thus maintain optimal functioning, thus being a fundamental factor that directly influences the development of individuals, because it directly intervenes in survival, physical growth, mental development, performance, productivity, health, and well-being throughout life, therefore, a good nutritional status guarantees the adequate and complete development of the capacities of individuals. Therefore, descriptive research with a quantitative, prospective cross- sectional approach was developed with the objective of determining the nutritional status and academic performance of preschool children from the Manuel José Rodríguez educational unit in the parish of Malacatos. The investigation was carried out on a sample of 32 children, which was equivalent to 100% of its population, the same ones that met the inclusion and exclusion criteria, from which the following statistics were obtained, first in relation to age 53, 13% of children are 4 years old, 40.63% of children are 5 years old; On the other hand, in relation to gender, 56.25% are male and the remaining 43.75% are female; In addition, of 100% of the students, 50% of them presented malnutrition and 6.25% were overweight; Likewise, 65.63% achieved the required learning (AAO), with averages less than 9 points, and 34.38% managed to master the required learning (DAR). Finally, when analyzing the variables, the relationship between nutritional status and academic performance was established through the chi square test, in which it was found that there is no statistically significant relationship between nutritional status and academic performance of students. However, it was concluded that overweight and malnourished students only achieve the required learning, when the ideal is that they master the required learning.